PENGGUNAAN TEKNIK DESENSITISASI SISTEMATIS UNTUK MENGURANGI KECEMASAN SISWA PADA SAAT PRESENTASI - Ferlysta Ayu Febbyanti; Giyono Giyono; Diah Utaminingsih (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this study was to determine whether students' anxiety during a presentation can be reduced by desensitization techniques systematically for class X students of SMK Negeri 1 Metro in the academic year 2012/2013. The problem In this study is that students who experience anxiety at the time of presentation. The problem in this research is "whether the anxiety of students during a presentation can be reduced by systematic desensitization techniques for class X students of SMK Negeri 1 Metro in the academic year 2012/2013?"..The method used in this research is a quasi experimental design with one-group pretest-posttest. Subjects of this study five students of class X who experience anxiety at the time of presentation. Data collection techniques in this study using observation. Based on calculations by the 5% significance test obtained p value = 0.043, p 0.05. So there is a significant difference in students 'anxiety during a presentation before and after implementation of systematic desensitization techniques. Thus Ha is accepted, which means anxiety students during a presentation can be reduced by systematic desensitization techniques. The conclusion of this research is the anxiety of students at the time of the presentation can be reduced by systematic desensitization techniques for class X students of SMK Negeri 1 Metro Academic Year 2012/2013. The advice given is (1)students who experience anxiety to consult the teacher guidance and counseling in order to help. (2)Guidance and Counseling teachers should help students who are experiencing anxiety by systematic desensitization techniques. (3)To the researchers should research first before determining there search title.Kata kunci: presentasi,kecemasan siswa, teknik desentisasi sistematis